Macroprudential Policy and Credit Supply - José-Luis Peydró (Swiss Journal of Economics and Statistics, 2016)
In this paper we analyze financial crises, and the interactions of macroprudential policy and credit. Financial crises are recurrent systemic phenomena, often-triggering deep and long-lasting recessions with large reductions in aggregate welfare, output and employment. Importantly for policy, systemic financial crises are typically not random events triggered by exogenous events, but they tend to occur after periods of rapid, strong credit growth. Moreover, a credit crunch tends to follow in a financial crisis with negative aggregate real effects. Macroprudential policy softens the credit supply cycles, with important positive effects on the aggregate real economy in crisis times.
Keywords: E58; G01; G21; G28; 330; financial crises; macroprudential policy; credit supply; risk-taking; capital; liquidity